2012
DOI: 10.7314/apjcp.2012.13.11.5777
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α-308 and -238 Polymorphisms with Risk of Cervical Cancer: A Meta-analysis

Abstract: Published data on the associations between tumor necrosis factor-alpha (TNF-α) promoter -308G>A and -238G>A polymorphisms and cervical cancer risk are inconclusive. To derive a more precise estimation of the relationship, a meta-analysis was performed. Data were collected from MEDLINE and PubMed databases. Crude odds ratios (ORs) with 95% confidence intervals (CIs) were calculated in a fixed/random effect model. 13 separate studies including 3294 cases and 3468 controls were involved in the meta-analysis. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The hRAD54 , hMSH2 , ABCB1 , ABCC5 , COL18A1 , and SLC19A1 genes were consistent with lymphoma and leukemia in Latin Americans [153,154,155,156], as well as some Caucasians and Asians [157,158,159,160]. The RB1 gene was related with retinoblastoma in Latin Americans [161,162], and the TNFα and TP53 genes with cervical cancer [163,164,165,166,167,168]. …”
Section: Germline Cancer Predisposition In Latin Americamentioning
confidence: 99%
“…The hRAD54 , hMSH2 , ABCB1 , ABCC5 , COL18A1 , and SLC19A1 genes were consistent with lymphoma and leukemia in Latin Americans [153,154,155,156], as well as some Caucasians and Asians [157,158,159,160]. The RB1 gene was related with retinoblastoma in Latin Americans [161,162], and the TNFα and TP53 genes with cervical cancer [163,164,165,166,167,168]. …”
Section: Germline Cancer Predisposition In Latin Americamentioning
confidence: 99%
“…TNF polymorphism is associated with increased risk of cervical cancer (Liu et al, 2012). Very interestingly TNF-α gene polymorphism can increase or decrease the susceptibility to cervical cancer depending on whether it is TNF-α-238A allele or TNF-α-308G>A which is altered (Pan et al, 2012).…”
Section: Tnfmentioning
confidence: 99%
“…It has also been demonstrated that basal levels of IL-10 are augmented in the peripheral blood mononuclear cell of patients with SIL [30]. Serum levels of IL-10 were observed to be significantly higher in women with invasive cervical cancer and high grade CIN as compared to controls [5].…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 93%
“…In India, the age standardized cervical cancer incidence and mortality rates were 27 and 15 per 100,000 women [4]. Cervical cancer is considered as a complex multi-step, multifactor process, and carcinogenesis occur as a result of multiple gene-environmental interactions [5]. A number of epidemiologic and molecular biologic data revealed that high-risk human papillomavirus (HPV) infection is the most well established environmental risk factor which is confirmed in 95%-100% cases for cervical cancer [6].…”
Section: Introductionmentioning
confidence: 99%